(untitled) (American Journal of Islam and Society, 1991)
Most of the world’s Muslims reside in countries where they are numerically predominant. As such, these Muslims possess a majoritarian outlook in sharp contrast to the perspective of minority Muslims living in India, China, the USSR, and some Western countries. In recent years, Muslim minorities have found themselves at the confluence of diverse social forces and political developments which have heightened their sense of communal identity and apprehension vish-vis non-Muslim majorities. This has been particularly true of the crisis besetting the Indian Muslims in 1990-91 as well as the newly formed Muslim communities in Western Europe. The foregoing circumstances have highlighted the need for serious research on Muslim minorities within a comparative framework. What follows is a preliminary outline of a research framework for a comparative study of Muslim minorities using the Indian Muslims as an illustrative case. The Salience of Tradition One of the most significant transnational phenomena in the four decades since mid-century has been the revival of communal consciousness among minorities in a large number of countries throughout the world. This tendency toward cultural regeneration has been noted among such diverse ethnic groups as Afro-Americans, French Canadians, Palestinian Arabs, the Scots of Great Britain, Soviet minorities, and native Americans. A common tendency among these groups is to reach back to their cultural traditions and to explore those roots which have served as the historical anchors of their present communal existence. Significantly, this quest for tradition has had a salutary impact upon the lives of these communities, for it has reinforced their collective and individual identities and has enabled them to confront the multiple difficulties of modem life more effectively. By according its members a sense ...